Illnesses of the will in ‘pre-psychiatric’ times - Haack, Kathleen; Kumbier, Ekkehardt; Herpertz, Sabine (History of psychiatry, 2010)
Since its emergence as a medical discipline in its own right, i.e. since the end of the eighteenth century, disorders of the will have constituted a major area of interest for psychiatrists. But even before then, in ‘pre-psychiatric’ times so to speak, there were occasional descriptions of illnesses of the will or, in the nomenclature used at the time, ‘ambiguous emotional states of minds’. This study presents some very early attempts to tackle and explain the problems of amentia occulta, manie sans délire and monomania in German literature, concentrating on works written from a medical and philosophical perspective. Beginning with the differentiation between will and reason, this study explores some concepts in which the will was perceived as a possible cause of mental illness and thus became a topic of medical interest.
Gesehen am 07.06.2023